2019
DOI: 10.1155/2019/7078024
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Health Effects of Benzene Exposure among Egyptian Taxi Drivers

Abstract: Objectives To study environmental exposure to benzene as well as hematological effects of benzene exposure in taxi drivers. Background Exposure to benzene has been associated with adverse health effects, including haematopoietic disorders. Methods A retrospective cohort study was carried out from the beginning of April 2017, through the end of June 2018, on 280 taxi drivers (the exposed group) and 120 unexposed matched individuals (controls). The tools included a predesigned self-administered questionnaire whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 28 publications
5
19
0
4
Order By: Relevance
“…Table 4, 5 These ndings come in agreement with previous studies conducted by Abozer et al, (16) Alfadaly et al, (19) and Liu et al (20) who con rmed signi cantly higher lymphocyte count and lymphocytosis among long-term benzene exposure. The same results recorded in the previous studies (21,22) regarding increased MCHC. However, other studies stated decreased RBCs counts in participants exposed to benzene compared with the non-exposed groups conversely the increased RBCs count ndings in this study.…”
Section: Categorysupporting
confidence: 90%
See 2 more Smart Citations
“…Table 4, 5 These ndings come in agreement with previous studies conducted by Abozer et al, (16) Alfadaly et al, (19) and Liu et al (20) who con rmed signi cantly higher lymphocyte count and lymphocytosis among long-term benzene exposure. The same results recorded in the previous studies (21,22) regarding increased MCHC. However, other studies stated decreased RBCs counts in participants exposed to benzene compared with the non-exposed groups conversely the increased RBCs count ndings in this study.…”
Section: Categorysupporting
confidence: 90%
“…However, other studies stated decreased RBCs counts in participants exposed to benzene compared with the non-exposed groups conversely the increased RBCs count ndings in this study. (19,21,23,24) Furthermore, the study results illustrated in Table 4 and Table 5 showed a signi cant reduction in the means of PCV, Hb, MCH, MCV, PLTs count, Monocyte counts, and the Neutrophil counts among benzene station workers compared with the healthy individuals. These ndings are in agreement with many studies (21,23,25) reported a decrease in PLTs count and decreases in MCH among benzene exposure workers and with the study, (26) who reported a reduction in Hb concentration.…”
Section: Categorymentioning
confidence: 94%
See 1 more Smart Citation
“…Diabetes is a major public health problem that is approaching epidemic proportions globally, and pollutants in the air or at home have been associated with diabetes [54]. Benzene exposure through the human lifespan is inevitable [6][7][8][9][10]. Drinking contaminated water or eating food that has been exposed to contaminated water, smoking cigarettes, or breathing secondhand cigarette smoke, exposure to e-cigarettes vaping, use of paint or detergent products, vehicle exhaust or gasoline, it's all part of the daily routine [55].…”
Section: Discussionmentioning
confidence: 99%
“…Benzene concentrations vary depending on geographic location [4,5], duration or route of exposure, and individual susceptibility factors such as age, gender or lifestyle. Various sources of benzene exposure include drinking contaminated water or food, smoking cigarettes, breathing secondhand cigarette smoke, vehicle exhaust or petroleum fuels, vaping e-cigarettes, using paint or detergent products [6][7][8][9][10][11][12][13][14]. While values of ambient benzene air concentrations in the U.S. have typically been <1 ppm (parts per million), significantly higher levels can be experienced as a result of various environmental factors [15] [16].…”
Section: Introductionmentioning
confidence: 99%